Ordinary clay as a support of nickel catalyst for steam reforming of acetic acid: Impacts of pretreatments of clay on catalytic behaviors. (13th July 2020) - Gao, Zhiran; Zhang, Zhanming; Tian, Hongli; Xu, Qing; Xu, Zhixiang; Li, Bin; Liu, Qing; Li, Cuncheng; Chen, Guozhu; Hu, Xun
Summary: Ordinary clay is a widely distributed and abundantly available material with the potential use as support of nickel catalysts with low cost. For the steam reforming of acetic acid, this study demonstrated the feasibility of ordinary clay as carrier of nickel catalyst. The pretreatment of the clay via impregnation with H2 SO4, leaching with H2 SO4 and pretreated with NaOH were carried out and the results indicated the substantial influences on physiochemical properties and catalytic behaviors of the catalysts. The Ni/Clay‐NaOH catalyst contained the most developed porous structures due to the formation of the water soluble Na4 SiO4 by the solid‐phase reaction between the SiO2 in clay and NaOH, which also rendered this catalyst with the superior catalytic activity. In addition, Ni/Clay‐NaOH catalyst also possessed the higher capability to gasify the reactive intermediates such as CCC and CO species as well as the CC species formed from the dissociative adsorption of acetic acid. This resulted in Ni/Clay‐NaOH catalyst with the highest resistivity toward coking. The varied treatment of the ordinary clay also was the reason of the coke formed with the distinct morphologies such as the amorphous coke with layered structure, the carbon‐nanotube form coke with single/multiple channels, defective structures, and varied sizes.